Dream jobs [engineering career]. - Cherry, S. (IEEE spectrum)
This paper features the Dream Jobs 2006 special report which lists 10 people who have found success in a variety of engineering disciplines. A common motif of these 10 successful engineers is that, when the right opportunities came along, they simply listened to both their guts and their hearts.